Seasonality Modifies the Effect of a Lipid-Based Nutrient Supplement for Pregnant Rural Women on Birth Length. Issue 3 (14th January 2015) - Toe, Laeticia C; Bouckaert, Kimberley P; De Beuf, Kristof; Roberfroid, Dominique; Meda, Nicolas; Thas, Olivier; Van Camp, John; Kolsteren, Patrick W; Huybregts, Lieven F
Abstract: Background: Maternal nutritional status is a major determinant of low birth weight and fluctuates across seasons. Seasonality may influence the outcome of prenatal nutrition interventions that aim to enhance fetal growth. Objective: This study investigated seasonal modifications of the efficacy of a randomized controlled prenatal nutrition intervention trial in pregnant women to improve fetal growth in rural Burkina Faso. Methods: The second Micronutriments et Santé de la Mère et de l'Enfant study compared a lipid-based nutrient supplement (LNS) fortified with multiple micronutrients (MMNs) to an MMN supplement. Truncated Fourier series were used to characterize seasonality in birth outcomes. Models that included the Fourier series and newborn and maternal characteristics were used to assess seasonal effect modifications of prenatal supplementation on birth outcomes. Results: Birth weight, birth length, small for gestational age as a proxy for intrauterine growth retardation, and preterm birth were significantly related to date of birth and showed important seasonal variations. LNSs, which supply energy in addition to MMNs, resulted in a significant increase in birth length (+13.5 mm, 95% CI: 6.5, 20.5 mm) at the transition from rain to dry season (September to November) compared to MMNs alone. Conclusions: The climatologic and agricultural seasonal patterns in Burkina Faso affect the efficacy of prenatal LNSs on birth length. In this context, prenatal MMN supplementation programs should be complemented by energy supplementation during the annual rain season to promote fetal growth. This trial was registered at clinicaltrials.gov as NCT00909974.